Pemahaman Guru Pendidikan Anak Usia Dini Terhadap Perencanaan Pembelajaran Tematik - Helly Apriyanti (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2017)
The purpose of this research is to describe the understanding of early childhood education teachers on thematic learning planning. The focus of this research is the extent to which early childhood education teachers understand about thematic learning planning. This research is a descriptive research conducted at Raudhatul Athfal (RA) Se-Kecamatan Ajung. The population in this research are teachers of RA Se-Kecamatan Ajung where the sample selection is done by simple random sampling. Data collection tool in this research by using questionnaire. From the result of data analysis, it can be concluded that the average of early childhood teacher's understanding on thematic learning planning is 76%, so that it can be categorized that the teacher has understood the aspect of thematic learning planning.